Bioactive Triterpenoids from Salvia Species - Topcu, G (Journal of natural products (Washington, D.C.), 2006)
Salvia species are important medicinal and culinary plants, and they have been the subject of numerous chemical and biological studies. The bioactive triterpenoids of Salvia species, reported in the literature to date, are reviewed. About 200 triterpenoids, almost 80 of which are new, isolated, and characterized from about 100 Salvia species, are presented herein. In addition to the diverse biological activities of the pure triterpenoids, studies on biological activity of extracts of Salvia species are also described.